До питання про переселення французької аристократії на Південь України наприкінці XVIII – початку XIX ст. - Сидорович, Є. (Краєзнавство, 2018)
У статті проводиться аналіз початку активного заселення французькими дворянами території
Північного Причорномор'я. Виділяються причини та наслідки переговорів А.Е. де Ришельє з урядом
Російської імперії, що суттєво вплинуло на переселенський рух аристократії. Окремо автор аналізує
діяльність комерції радника В. Рув'є, як приклад господарського освоєння регіону європейцями. In the article made an analysis of the active population of the beginning of the French nobles in the South
of Ukraine. Stand out the causes and consequences A.E de Richelieu with the Government of the Russian Empire,
which greatly influenced the migration movement aristocracy. Separately, the author analyzes the activities
of commerce adviser V. Rouvier, as an example of economic development of the European region. The second
half of the XVIII century was a turning period in the history of France, which was associated with the beginning
of the revolution in 1789. This fact led to the beginning of the resettlement movement royal aristocracy abroad,
as a certain part of this class does not support the political changes in the country, and saw in them only the
destruction of the state. A certain number of representatives of the nobility found their refuge in the Russian
Empire, as the governments of other countries of Western Europe, they denied it. The nobles were forced to
seek refuge in Europe. This was due to the defeat of the first anti-French coalition forces. Namely, it was forbidden
to be expeditionary corps of Prince Conde in Prussia and Austria. Some of them have been invited by
the Empress Catherine II, which began to attract them to the development of the sparsely populated parts of
the south-western Russia. В статье осуществляется анализ начала активного заселения французскими дворянами территории Северного Причерноморья. Выделяются причины и последствия переговоров А.Э. де Ришелье с правительством Российской империи, что существенно повлияло на переселенческое движение аристократии. Отдельно автор анализирует деятельность коммерции советника В. Рувье, как пример
хозяйственного освоения региона европейцами.